Fulfilling the Marrakesh Mandate on Coherence: Ten years of cooperation between the WTO, IMF and World Bank - Marc Auboin (World Trade Organization (WTO), 2007)
Contributing to achieving more coherent global economic policy-making is one of the five core functions of the WTO, as defined by Article III.5 of the WTO Agreement. Its ability to do so depends on it carrying out its other functions successfully - providing a forum for liberalization, ensuring a strict observance of its multilateral rules and disciplines, and contributing to policy surveillance. In 1994, WTO Members added to the WTO Agreement a Ministerial Declaration On Achieving Greater Coherence in Global Economic Policy Making, calling on the WTO to cooperate with the IMF and the World Bank to this aim. Of course, cooperation is not confined to these three institutions. The WTO works intensively with other UN institutions. However, the WTO Coherence Mandate stems from the desire to link up these three multilateral economic organizations, which share the same aim (improving living standards, achieving sustainable development, contributing to expand international trade), of policy coherence. This paper shows that in ten years of cooperation the three organizations have built much tighter links than under the GATT, allowing for a better articulation of trade, financial and debt policies. However, the experience also shows that, as indicated in the Declaration, policy coherence must be achieved at home first; inter-agency cooperation can only improve the coordination and articulation of policies, not correct basic policy inconsistencies at country level. While at the present moment the focus of the tripartite cooperation is how to mainstream development into trade (in the context of the Doha Development Agenda (DDA)), the relationship between trade and finance remains equally important, and not only at times of financial crises. The flexible implementation of the Coherence Mandate has served the WTO and its partners well, and more cooperation for better coherence can be envisaged in the context of evolving architectures of the respective institutions. Examples of future, possible border-line issues to be treated as a matter of common interest are provided in the second part of this paper.
Keywords: 330; coherence; cooperation in global economic policy making; economic policy coordination; cooperation between international organizations